THE EFFECT OF PRODUCT QUALITY AND PRICE ON SALES IN “SAPARDI” BAKSO IN GAYUNGAN JEMUR - Kusmayati, Nindya Kartika; Aldieniyah, Zahro (International Business Management - Universitas Ciputra, 2020)
This research is a quantitative study that aims to answer the question of whether product quality and price affect the sales level of the“SAPARDI” meatballs in Jemur Gayungan street. This research uses thequantitative method with a customer satisfaction survey approach. The sampling technique in this study was purposive sampling, with 78 respondents.Data collection technique used questionnaires and were processed usingSPSS statistics 16. The results showed that the quality of the product had apartially positive but not significant effect, meaning that it had an effectbut it was very small and it was necessary to make creative ideas for itsproducts. Price has a positive and significant effect, meaning that price isone of the reasons customers buy Sapardi meatballs. There is a simultaneous influence between product quality and price variables on the SalesLevel of the “SAPARDI” Meatballs in Jemur Gayungan but the effect is nottoo significant, so it is necessary to do further research using other variables.